Penerapan Aplikasi Sistem Keuangan Desa Berdasarkan Peraturan Menteri Dalam Negeri Nomor 20 Tahun 2018 Dalam Upaya Meningkatkan Kualitas Pelaporan Keuangan Desa Ngadimulyo Kecamatan Kampak Kabupaten Trenggalek - Ida Ayuningtyas Zholaikah Katinem (Accounting and Finance Studies, 2022)
At this time, technology has developed rapidly all over the world. All organizations are competing to improve the quality of their organization. In order to improve the quality of village financial management, BPKP has developed the Siskeudes application. The purpose of this study was to determine the quality of financial reporting in Ngadimulyo Village after the Siskeudes application was implemented. This research is a qualitative one using a descriptive approach. The results showed that the quality of financial reporting in Ngadimulyo Village was classified as good after implementing the Siskeudes application. Although there are still obstacles in human resources. The Ngadimulyo Village Government has implemented Permendagri Number 20 of 2018. Transparency in Ngadimulyo Village is manifested in the form of banners related to the Village Revenue and Expenditure Budget (APBDes) in several places and also uploaded on the village website. Accountability in Ngadimulyo Village at the reporting stage has also used two versions, namely online using the Siskeudes application and also physically. In terms of participation, the community has also channeled their aspirations although there are still many people who are indifferent to activities in the village. For orderliness and discipline, the budget has also been realized in timely financial reporting, although sometimes there are still shifts.